Lipid balance must be just right to prevent development of severe liver damage - Timothy F. Osborne; Peter J. Espenshade (The Journal of Clinical Investigation, 2022)
Nonalcoholic fatty liver disease (NAFLD) is a major health concern that often associates with obesity and diabetes. Fatty liver is usually a benign condition, yet a fraction of individuals progress to severe forms of liver damage, including nonalcoholic steatohepatitis (NASH) and hepatocellular carcinoma (HCC). Elevated sterol regulatory element–binding protein–driven (SREBP-driven) hepatocyte lipid synthesis is associated with NAFLD in humans and mice. In this issue of the JCI, Kawamura, Matsushita, et al. evaluated the role of SREBP-dependent lipid synthesis in the development of NAFLD, NASH, and HCC in the phosphatase and tensin homolog–knockout (PTEN-knockout) NASH model. Deletion of the gene encoding SREBP cleavage–activating protein (SCAP) from the liver resulted in decreased hepatic lipids, as expected. However, SCAP deletion accelerated progression to more severe liver damage, including NASH and HCC. This study provides a note of caution for those pursuing de novo fat biosynthesis as a therapeutic intervention in human NASH.